Trade Facilitation and the Extensive Margin - Maria Persson (Research Institute of Industrial Economics (IFN), 2010)
The literature on trade facilitation has mostly focused on implications for trade volumes. However, recent theoretical contributions have emphasized that trade costs - such as transaction costs related to cross-border trade procedures - affect both the traded volumes of "old" goods (the intensive margin) and the range of traded goods (the extensive margin). This paper therefore tests whether trade facilitation affects the extensive margin by counting the number of 8-digit products that are exported from developing to EU countries, and using this as the dependent variable in an estimation. Moreover, it also tests whether the extensive margins in differentiated and homogeneous goods are affected in the same way by transaction costs. Estimation results suggest that if export transaction costs - proxied by the number of days needed to export a good - declined by 1 per cent, the number of exported differentiated and homogeneous products would rise by 0.7 and 0.4 per cent respectively. Policy simulations further illustrate that if all countries were as efficient at the border as the most efficient country at the same level of development, the number of exported differentiated and homogeneous products would increase by 64 and 29 per cent respectively.
Keywords: C21; F13; O24; 330; Trade Facilitation; Extensive Margin; Export Diversification; Differentiated Products; Homogeneous Products; European Union; Developing Countries; Handelsliberalisierung; Exportdiversifizierung; Transportkosten; Entwicklungsländer; EU-Staaten